2022
DOI: 10.3389/fnagi.2022.873032
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Brain Magnetic Resonance Imaging Indices in the Association of Olfactory Identification and Cognition in Chinese Older Adults

Abstract: BackgroundOlfactory identification dysfunction frequently occurs in individuals with cognitive decline; however, a pathological mechanism linking the two has not been discovered. We aimed to study the association between olfactory identification and cognitive function, and determine the effects of brain regions atrophy therein.MethodsA total of 645 individuals (57.5% were female) from the Taizhou Imaging Study, who underwent cognitive and olfactory identification measurements, were included. A subsample of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Previous studies also found significant relationships between olfaction and neurodegenerative indicators, such as brain atrophy and hypometabolism, total tau protein (t‐tau), and NfL. Olfactory scores were found to be associated with magnetic resonance imaging‐measured volumes, mainly in AD‐signature regions, such as hippocampal, temporal lobe, entorhinal regions, and amygdala 6,14–17,43 . In addition, hypometabolism in olfactory regions, measured by fluorodeoxyglucose positron emission tomography, was also shown to have a significant association with odor identification scores 15 .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Previous studies also found significant relationships between olfaction and neurodegenerative indicators, such as brain atrophy and hypometabolism, total tau protein (t‐tau), and NfL. Olfactory scores were found to be associated with magnetic resonance imaging‐measured volumes, mainly in AD‐signature regions, such as hippocampal, temporal lobe, entorhinal regions, and amygdala 6,14–17,43 . In addition, hypometabolism in olfactory regions, measured by fluorodeoxyglucose positron emission tomography, was also shown to have a significant association with odor identification scores 15 .…”
Section: Discussionmentioning
confidence: 84%
“…Olfactory scores were found to be associated with magnetic resonance imagingmeasured volumes, mainly in AD-signature regions, such as hippocampal, temporal lobe, entorhinal regions, and amygdala. 6,[14][15][16][17]43 In addition, hypometabolism in olfactory regions, measured by fluo-rodeoxyglucose positron emission tomography, was also shown to have a significant association with odor identification scores. 15 Longitudinally, higher olfactory scores were related to slower brain atrophy in the entorhinal cortex and hippocampus.…”
Section: Discussionmentioning
confidence: 95%
“…Even altered olfactory identification function has been detected in subjective cognitive decline (SCD), a stage that occurs before MCI (Jobin et al, 2021b ). A recent study provided evidence that the amygdala (a component of the POC) functions as a shared neural substrate linking olfactory identification ability with cognitive function (Shao et al, 2021 ; Tan et al, 2022 ). Olfactory identification deficits were also detected in both AD and MCI.…”
Section: Discussionmentioning
confidence: 99%